Menanamkan Pendidikan Karakter Islami Untuk Anak Jalanan - Syamsul Muqorrobin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
This research aims to analyze the Role of Islamic Religious Education Teachers in Supporting the Spiritual Growth of Blind Orphans. The type of research used is literature review. Data retrieval techniques with documentation from journal data on Google Scholar. Data analysis technique using Systematic Literature Review. The research results of the role of Islamic religious education teachers in supporting the spiritual growth of blind orphans reveal that teachers have a crucial role in guiding and shaping the spiritual aspects of children who have experienced the loss of their parents and have limited vision. Teachers must be able to provide a deep and comprehensive understanding of the Islamic religion, while creating an inclusive and supportive learning environment. Apart from that, teachers must also be role models in the practice of religious life, provide emotional support, and facilitate the development of moral values. Thus, through the comprehensive role of teachers, blind orphans can grow and develop holistically, both spiritually and morally, so that they are able to face life's challenges with full confidence and integrity.